PROBLEMS IN KINDERGARTEN - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Preschool education - the upbringing and education of young children (ECCE) - is the aspects of children’s health, nutrition and hygiene that contribute to their survival, growth, development and education. speech, physical, socio-personal, and artistic-aesthetic development - from birth to formal and informal, formal and informal to elementary school enrollment. The ECD approach, which is mainly aimed at achieving a normal standard of living for young children, is also important in terms of adult development. is to help.